Monitoring and Predicting Treatment Response of Extraocular Muscles in Grave's Orbitopathy by 99mTc-DTPA SPECT/CT - Jiang, Chengzhi; Deng, Zilong; Huang, Jin; Deng, Haoyu; Tan, Jia; Li, Xinhui; Zhao, Min (Frontiers in Medicine, 2021)
Objective: To investigate single-photon emission computed tomography/computed tomography (SPECT/CT) for assessing inflammation in the extraocular muscles (EOMs) and predicting the therapeutic efficacy of periocular glucocorticoid therapy (PGT) for Grave's ophthalmopathy (GO). Materials and Methods: A total of 412 eyes from 206 patients with GO referred for 99mTc-DTPA orbital SPECT/CT were enrolled. Fourteen age- and gender-matched healthy controls (28 eyes) were included. The thickness and uptake ratio (UR) of four EOMs were derived from SPECT/CT. Eighty-six eyes from patients with GO patients received PGT. Changes in SPECT/CT parameters were evaluated between the pre- and post-treatment. Results: 195 eyes and 217 eyes were classified as active and inactive stages by clinical activity score (CAS). Values of the thickness and UR of each EOM, Tmax, and Umax were all significantly higher in the active GO than in the inactive GO and controls (p < 0.01). Among the 86 eyes (48 GO patients) included in the efficacy analysis, 56 eyes and 30 eyes were classified as responders and non-responders. Values of thicknesses and UR of each EOM, the maximum thickness (Tmax), and the maximum UR (Umax) all dropped following PGT in the responders (p < 0.01). Logistic regression analysis identified the Umax as an independent predictor for the responders (p < 0.01). Moreover, the Umax demonstrated incremental predictive value over clinical characters and CAS, as evidenced by the improved area under the curve (0.85 vs. 0.78) and global chi-square (34.12 vs. 18.1). Conclusion:99mTc-DTPA SPECT/CT has the potential to assess inflammatory activity by detecting the involvement of EOMs in GO. Pre-treatment UR provides independent and incremental values for the prediction of PGT treatment response.